Podding of Paralomis granulosa (Lithodidae) juveniles inhabiting kelp forests of the Cape Horn Archipelago (Chile) - Cañete Aguilera, Juan Ivan; Friedlander, Alan M.; Sala, Enric; Figueroa, Tania (My University, 2021)
Abstract Subtidal observations along the Cape Horn Archipelago, Chile (CHA) in February 2017 revealed an unusually large aggregation (or pod) of juvenile false king crabs, Paralomis granulosa (Hombron and Jacquinot, 1846), in association with kelp forests (Macrocystis pyrifera and Lessonia spp.). This is the first study to report a dense aggregation of juveniles of this crab, which was observed at Wollaston Island (WI) (~ 10 m). Paralomis granulosa was present on half the transects at WI (N=10), with a density of 3.1 ± 9.9 ind. m-2. Photographs from the podding event showed densities of P. granulosa ranging from 63 to 367 ind. plant-1 (190 ± 133 ind. plant-1). Juveniles (32.8 ± 7.3 mm carapace length) were recorded on kelp fronds, holdfasts, kelp stipes, and adjacent rocky bottom of this protected coast. This podding behavior resembles that of other juvenile king crabs in terms of homogeneity in size structure and may be a predator avoidance mechanism. These observations highlight three aspects of this kelp-animal relationship: (i) identification of a previously unknown ecosystem service provided by sub-Antarctic kelp forests to the associated benthic fauna; (ii) the ecological value of kelp as a bioengineering species; and (iii) pods being an important attribute for population assessments. Due to the importance of the CHA in the life cycle for this and other species, we suggest the archipelago be incorporated within the recently established Diego Ramírez Island-Drake Passage Marine Park.
Keywords: diego ramírez island-drake passage marine park; ecological recruitment; king crab ecology; seaweed-animal relationship; sub-antarctic benthos